PENINGKATAN PROSES DAN HASIL BELAJAR MATERI ORGAN PENCERNAAN DAN FUNGSINYA PADA HEWAN DAN MANUSIA DENGAN METODE GROUP INVESTIGATION - Sumadi Sumadi (Program Pascasarjana Universitas Islam Darul `Ulum Lamongan, 2021)
The purpose of this study was to improve the learning achievement of the natural science subject matter of digestive organs and their function in animals and humans in the fifth grade students of Banjarmadu Elementary School using the group investigation method. The research subjects were fifth grade students of Banjarmadu Elementary School with a total of 18 students. The research data was collected through written tests, student observation sheets and learning observation sheets and analyzed qualitatively descriptive. Based on the written test results of the first cycle it was obtained from the average value of 75 students with 11 students (61.1%) getting a value of ≥ 75 and 7 students (39%) getting a score of <75. Assessment of the management of learning using the group investigation method has not been maximal (60%) while students' responses to learning are also less than happy or less interested. Results in Cycle II students who scored <75% there were 2 students (11%) while students who scored ≥ 75 there were 16 students (89%) managing learning using the maximum group investigation method (100%) and student responses to learning as well very happy and interested.